Preparation method of copper-doped carbon nitride nano composite material and application of copper-doped carbon nitride nano composite material in electrocatalytic carbon dioxide reduction
Through copper-doped carbon nitride nanocomposite catalyst, the problem of poor catalyst selectivity in electrocatalytic carbon dioxide reduction is solved, and the efficient conversion of CO2 to ethanol and the improvement of C-C coupling activity is achieved, which significantly improves the catalytic performance.
Patent Information
- Application Number
- CN202411225922.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-03
- Publication Date
- 2024-12-27
AI Technical Summary
In the existing electrocatalytic carbon dioxide reduction system, there is a problem that the catalyst has poor selectivity for a single target product, especially that it is difficult for Cu-based catalysts to effectively inhibit the hydrogen evolution reaction and improve the C-C coupling activity during the CO2 reduction process.
The copper-doped carbon nitride nanocomposite material is used as catalyst to prepare carbon nitride precursors through melamine, and then calcined in an N2 atmosphere and washed with anhydrous ethanol to form a Cu-g-C3N4 catalyst, which significantly improves the adsorption performance of the intermediate and C-C coupling activity.
The efficient conversion of CO2 to ethanol in a wide voltage range is achieved, the Faraday efficiency of ethanol is greater than 50%, and the hydrogen evolution reaction is effectively inhibited, improving the selectivity of a single target product.
Smart Images

Figure CN119191239A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electrocatalytic carbon dioxide reduction materials, and in particular relates to a method for preparing a copper-doped carbon nitride nanocomposite material and application of the copper-doped carbon nitride nanocomposite material in electrocatalytic carbon dioxide reduction. Background Art
[0002] The resource utilization approach of carbon dioxide (CO2) centered on the electrochemical reaction of CO2, including CO2 batteries and CO2 electrocatalytic reduction, is an important technical means to support the realization of the "dual carbon goals".
[0003] Among them, CO2 electrocatalytic reduction reaction (CO2RR) can not only consume redundant CO2 in the atmosphere and supplement the carbon cycle, but also generate high value-added fuels and chemical raw materials, such as carbon monoxide (CO), formic acid (HCOOH), ethanol (C2H5OH), etc., which is of great significance to the solution of climate problems and the national economy, and has ideal application prospects and important research value.
[0004] Since CO2RR has a huge reaction energy barrier and high complexity, most of the research work on CO2RR focuses on the design of catalysts and catalytic interfaces. Among them, metal-nitrogen-carbon (MNC) as catalytic active sites has many advantages such as high atomic utilization, controllable coordination structure, and outstanding performance. It has been widely studied and is considered to be a potential frontier direction for the development of efficient electrochemical materials.
[0005] So far, Cu is one of the few metals that can reduce CO2 to high value-added multi-carbon products (such as C2H4, C2H5OH and n-C3H7OH, etc.). Compared with C1 products, multi-carbon products have higher economic value and practical significance.
[0006] Cu can inhibit the hydrogen evolution reaction (HER) to a certain extent and the intermediate product CO * The adsorption energy moderate, and Cu-based catalysts can enhance CO * Hydrogenation or CC coupling of intermediate products. In the eCO2RR with the participation of Cu-based catalysts, there is a considerable product distribution, but the selectivity of a single target product is poor.
[0007] Based on the defects of catalysts in the current electrocatalytic carbon dioxide reduction system, it is necessary to improve it. Summary of the invention
[0008] In order to overcome the above problems, the present invention provides a method for preparing a copper-doped carbon nitride nanocomposite material and its application in electrocatalytic carbon dioxide reduction. The present invention uses melamine to prepare a carbon nitride precursor, and uses Cu(CH3COO)2·H2O as a source of metallic copper to prepare a copper-doped carbon nitride material. The structure of the electrocatalyst can be finely and reasonably designed to significantly affect the adsorption performance of some key intermediates, thereby affecting the inherent reaction pathway, and obtaining a single target product with higher selectivity.
[0009] To achieve the above object, the present invention adopts the following technical solutions:
[0010] A method for preparing a copper-doped carbon nitride nanocomposite material, characterized in that it comprises the following steps:
[0011] Step 1: Preparation of carbon nitride precursor
[0012] 1.1 Dissolve melamine in deionized water to obtain an aqueous solution of melamine;
[0013] 1.2 Then, a metallic copper salt is added to the aqueous solution of melamine and stirred to obtain a mixture;
[0014] 1.3 raising the temperature of the mixture to 100° C. to evaporate water, and after the water is evaporated and removed, drying is performed to obtain a carbon nitride precursor;
[0015] Step 2: Preparation of copper-doped carbon nitride nanocomposites
[0016] 2.1 Finely grind the obtained carbon nitride precursor, and heat and calcine under the protection of N2 atmosphere to obtain the product;
[0017] 2.2 After the product of step 2.1 is cooled to room temperature, the product is washed multiple times with deionized water and anhydrous ethanol to obtain the preparation of copper-doped carbon nitride nanocomposite material.
[0018] Furthermore, in the step 1.1, melamine is dissolved in deionized water at 80° C., and the addition ratio of melamine to deionized water is 1.0-3.0 g: 25-100 mL.
[0019] Furthermore, in the step 1.2, after the copper metal salt is added to the melamine water solution, the mass fraction of the copper metal salt is 1-5%; the stirring time is 30-40 minutes;
[0020] In the step 1.3, after the water is evaporated away, the mixture is dried in an oven at 60°C.
[0021] Furthermore, in the step 2.1, the temperature is raised and calcined at a heating rate of 5-10°C / min to 500-550°C and calcined for 3-6 hours.
[0022] Furthermore, in the step 2.2, the product is washed multiple times with deionized water and anhydrous ethanol, that is, washed three times with deionized water and washed twice with anhydrous ethanol.
[0023] The invention also discloses a copper-doped carbon nitride nanocomposite material, which is characterized in that it is prepared according to the above preparation method.
[0024] The present invention also discloses an application of the copper-doped carbon nitride nanocomposite material in electrocatalytic carbon dioxide reduction, wherein the copper-doped carbon nitride nanocomposite material is used as a catalyst to prepare an electrode material for electrocatalytic carbon dioxide reduction.
[0025] Furthermore, the specific operation of the application includes the following steps:
[0026] The copper-doped carbon nitride nanocomposite material is dispersed in a mixed solution of ethanol and naphthol film ethanol dispersion, and drop-coated on carbon paper as a working electrode, an Ag / AgCl electrode as a reference electrode, and a platinum sheet as a counter electrode;
[0027] The cathode electrolyte is a bicarbonate solution saturated with CO2.
[0028] Furthermore, the cathode electrolyte is one of 0.1-1M KHCO3 solution, NaHCO3 solution, CSHCO3 solution, and LiHCO3 solution.
[0029] Furthermore, the loading amount of the copper-doped carbon nitride nanocomposite material is 0.5-2 mg / cm 2 .
[0030] In the application of the present invention, the cathode electrolyte may preferably be a 0.1-1 M KHCO3 solution.
[0031] In the application of the present invention, the naphthol membrane ethanol dispersion Nafion is generally D520, that is, naphthol with a mass fraction of 5% is dispersed in an ethanol solution.
[0032] In the application of the present invention, the specific operation method involves the preparation of the working electrode:
[0033] The method is to mix 10 mg of copper-doped carbon nitride nanocomposite catalyst with 470 μL of anhydrous ethanol, 475 μL of deionized water and 50 μL of Nafion solution (5 wt% Nafion ethanol dispersion), and then ultrasonicate for 1 hour to form a uniform catalyst ink. 200 μL of the obtained catalyst ink is added dropwise to carbon paper (1×2 cm 2 ) and dried directly at 50°C for 1 h.
[0034] The copper-doped carbon nitride nanocomposite material prepared by the present invention has more excellent properties:
[0035] In a CO2-saturated 0.5 M KHCO3 solution, the applied potential ranged from -0.8 to -1.1 V (vs. RHE), and the CO2 reduction catalysis of g-C3N4 was mainly to CO, with the highest Faraday efficiency of CO reaching 41%. This is because the g-C3N4 structure contains a large amount of pyridinic nitrogen, which is very effective for CO * The binding energy of is weak and it helps the desorption of CO, so the selectivity of CO is very high.
[0036] The Cu-g-C3N4 catalyst can effectively inhibit the hydrogen evolution reaction at low applied potential and shows high selectivity for C2H5OH. At a potential of -0.9 V (Vs.RHE), the ethanol Faradaic efficiency reaches 53.44%.
[0037] This result shows that the tandem catalysis of Cu and carbon nitride can effectively improve the performance of copper-based catalysts in reducing CO2 to C 2+ Activity and selectivity of the product ethanol.
[0038] The copper-doped carbon nitride nanocomposite material prepared by the present invention has excellent catalytic performance, and its mechanism is:
[0039] Due to the typical characteristics of wrinkled and layered graphite phase carbon nitride, the catalyst has a large electrochemically active surface area and a fast electron transport capability. By doping with copper metal elements, the electronic structure of carbon nitride is effectively regulated, and Cu is in a lower oxidation state Cu δ +(0<6<2), which is conducive to the occurrence of CC coupling process, thereby significantly improving the catalytic activity and ethanol selectivity.
[0040] The present invention has the following beneficial effects:
[0041] 1. The copper-doped carbon nitride nanocomposite material prepared by the present invention utilizes the interlayer stacking of g-C3N4 aromatic fragments to load metallic copper single atoms, which can increase the specific surface area while making Cu in a stable oxidation state. The presence of metallic copper single atom sites promotes CC coupling.
[0042] 2. The preparation method of the present invention is simple, does not require too much equipment, and the raw materials are relatively easy to obtain and can be easily mass-produced.
[0043] 3. The copper-doped carbon nitride nanocomposite material prepared by the present invention can realize the efficient conversion of CO2 to ethanol, and the Faraday efficiency is greater than 50% in a wide voltage range, and has broad application value. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] Figure 1 : SEM images of the carbon nitride and copper-doped carbon nitride nanocomposite materials prepared in Example 1 of the present invention and the carbon material prepared in Comparative Example 1;
[0045] Figure 2 : TEM image of the copper-doped carbon nitride nanocomposite material prepared in Example 1 of the present invention;
[0046] Figure 3 : FTIR images of carbon nitride and copper-doped carbon nitride nanocomposite materials prepared in Example 1 of the present invention;
[0047] Figure 4 : XPS graph of metallic copper of the copper-doped carbon nitride nanocomposite material prepared in Example 1 of the present invention;
[0048] Figure 5 : LSV curve of electrocatalytic CO2 reduction of carbon nitride and copper-doped carbon nitride nanocomposite prepared in Example 1 of the present invention;
[0049] Figure 6 : Faraday efficiency diagram of the electrocatalytic CO2 reduction to ethanol of the carbon nitride and copper-doped carbon nitride nanocomposite prepared in Example 1 of the present invention at different voltages. DETAILED DESCRIPTION
[0050] The present invention will be further described below in conjunction with the accompanying drawings and embodiments:
[0051] In the embodiments of the present invention, unless otherwise defined, all professional terms used hereinafter have the same meanings as those generally understood by those skilled in the art.
[0052] Unless otherwise specified, various reagents and raw materials used in the present invention can be purchased from the market.
[0053] Example 1
[0054] Step 1: Preparation of carbon nitride precursor
[0055] 2.0 g of melamine was dissolved in 50 mL of deionized water at 80 ° C, and then 0.1571 g of Cu(CH3COO)2·H2O, with a mass fraction of 2.5% of the metal copper salt after addition, was added to the above solution and stirred for 30 minutes. The temperature of the mixture was raised to 100 ° C to evaporate water, and then dried in an oven at 60 ° C.
[0056] Step 2: Preparation of copper-doped carbon nitride nanocomposites
[0057] The obtained carbon nitride precursor was finely ground and calcined at 550° C. at a heating rate of 5° C. / min for 4 hours under the protection of N 2 atmosphere.
[0058] After cooling to room temperature, the product was washed several times with deionized water and anhydrous ethanol.
[0059] The copper-doped carbon nitride nanocomposite material Cu-g-C3N4 was obtained by washing with deionized water three times and with anhydrous ethanol twice. 2 .
[0060] The Cu-g-C3N4 prepared in Example 1 was used as a catalyst to effectively inhibit the hydrogen evolution reaction at a low applied potential and showed high selectivity for C2H5OH. At a potential of -0.9 V (vS.RHE), the Faraday efficiency of ethanol reached 53.44%.
[0061] Example 2
[0062] Step 1: Preparation of carbon nitride precursor
[0063] 1.0 g of melamine was dissolved in 100 mL of deionized water at 80 ° C, and then 0.1571 g of Cu(CH3COO)2·H2O, with a mass fraction of 5% of the metal copper salt after addition, was added to the above solution and stirred for 40 minutes. The temperature of the mixture was raised to 100 ° C to evaporate water, and then dried in an oven at 60 ° C.
[0064] Step 2: Preparation of copper-doped carbon nitride nanocomposites
[0065] The obtained carbon nitride precursor was finely ground and calcined at 500° C. at a heating rate of 10° C. / min for 3 hours under the protection of N 2 atmosphere.
[0066] After cooling to room temperature, the product was washed several times with deionized water and anhydrous ethanol.
[0067] The copper-doped carbon nitride nanocomposite material Cu-g-C3N4 was obtained by washing with deionized water three times and with anhydrous ethanol twice. 2.
[0068] The Cu-g-C3N4 prepared in Example 1 was used as a catalyst to effectively inhibit the hydrogen evolution reaction at a low applied potential and showed high selectivity for C2H5OH. At a potential of -0.9 V (vs. RHE), the ethanol Faradaic efficiency reached 51.95%.
[0069] Example 3
[0070] Step 1: Preparation of carbon nitride precursor
[0071] 3.0 g of melamine was dissolved in 25 mL of deionized water at 80 °C, and then 0.0943 g of Cu(CH3COO)2·H2O, with a mass fraction of 1% of the metal copper salt after addition, was added to the above solution and stirred for 30 minutes. The temperature of the mixture was raised to 100 °C to evaporate the water, and then dried in an oven at 60 °C.
[0072] Step 2: Preparation of copper-doped carbon nitride nanocomposites
[0073] The obtained carbon nitride precursor was finely ground and calcined at 550° C. at a heating rate of 8° C. / min for 6 hours under the protection of N 2 atmosphere.
[0074] After cooling to room temperature, the product was washed several times with deionized water and anhydrous ethanol.
[0075] The copper-doped carbon nitride nanocomposite material Cu-g-C3N4 was obtained by washing with deionized water three times and with anhydrous ethanol twice. 2 .
[0076] The Cu-g-C3N4 prepared in Example 1 was used as a catalyst to effectively inhibit the hydrogen evolution reaction at a low applied potential and showed high selectivity for C2H5OH. At a potential of -0.9 V (vS.RHE), the Faraday efficiency of ethanol reached 52.17%.
[0077] Comparative Example 1
[0078] 3 g of melamine was weighed and placed in an alumina crucible with a lid, and melamine was heated to 550°C in a muffle furnace at a heating rate of 5°C / min and maintained for 3 hours. After the insulation was completed, the temperature was naturally lowered to 30°C to obtain g-C3N4, which was light yellow in color.
[0079] Catalyst performance evaluation
[0080] All electrochemical measurements in this study were performed using an electrochemical station from Auto Lab in a typical three-electrode system. A custom-made gas-tight H-type cell was used, with a conventional three-electrode system consisting of carbon cloth (carbonpaper) with a catalyst coating, an Ag / AgCl reference electrode (3.5M KCl), and a Pt mesh counter electrode. A cation exchange membrane (Nafion-117) was used to separate the two compartments. The electrolyte at the cathode was a 0.5M KHCO3 solution.
[0081] Preparation of carbon paper working electrode:
[0082] 10 mg of copper-doped carbon nitride nanocomposite was mixed with 470 μL of ethanol, 475 μL of deionized water, and 50 μL of Nafion solution (5 wt %, Sigma-Aldrich), and then sonicated for 1 h to form a uniform catalyst ink.
[0083] Take 200 μL of the obtained catalyst ink and drop it twice onto carbon paper (1×2 cm 2 ) and dried directly at 50°C for 1 h.
[0084] The preparation of the comparative carbon paper working electrode was performed by simply changing the addition of 10 mg of copper-doped carbon nitride nanocomposite material to the g-C3N4 prepared in Comparative Example 1.
[0085] Analysis of the experimental results obtained:
[0086] The Cu-g-C3N4 prepared in Examples 1-3 was used as a catalyst to effectively inhibit the hydrogen evolution reaction at low applied potentials and showed high selectivity for C2H5OH. At a potential of -0.9 V (vs. RHE), the ethanol Faradaic efficiency was greater than 50%.
[0087] In a CO2-saturated 0.5 M KHCO3 solution, the applied potential ranged from -0.8 to -1.1 V (vs. RHE), and the CO2 reduction catalysis of g-C3N4 was mainly to CO, with the highest Faraday efficiency of CO reaching 41%. This is because the g-C3N4 structure contains a large amount of pyridinic nitrogen, which is very effective for CO * The binding energy of is weak and it helps the desorption of CO, so the selectivity of CO is very high.
[0088] The Cu-g-C3N4 catalyst has an ethanol Faraday efficiency of 53.44% at a potential of -0.9 V (VS.RHE). This result shows that the tandem catalysis of Cu and carbon nitride can effectively improve the copper-based catalyst to reduce CO2 to C 2+ Activity and selectivity of the product ethanol.
[0089] The various properties of the copper-doped carbon nitride nanocomposite material prepared by the present invention are further described by the accompanying drawings:
[0090] Figure 1 These are SEM images of the carbon nitride and copper-doped carbon nitride nanocomposite materials prepared in Example 1 of the present invention and the carbon material prepared in Comparative Example 1.
[0091] from Figure 1 It can be seen that the obtained g-C3N4 is a porous layered "organ" structure. After doping with Cu atoms, Figure 1 As shown in c and d, the microstructure of Cu-g-C3N4 is slightly different from that of g-C3N4, but still shows the typical characteristics of wrinkled and layered graphite phase carbon nitride.
[0092] Compared with g-C3N4, Cu-g-C3N4 has a fragmented morphology and a porous structure. This is because the deamination effect, which is enhanced by Cu doping, leads to more gas release.
[0093] Figure 2 This is a TEM image of the copper-doped carbon nitride nanocomposite material prepared in Example 1 of the present invention. Figure 2 It can be seen that Cu-g-C3N4 has a thin porous sheet structure. According to existing literature reports, such a well-developed porous structure and the characteristics of different types of pores in multi-directional channels play an important role in the CO2 reduction reaction. Figure 2 b shows that there are a large number of bright spots distributed in the Cu-g-C3N4 layer, proving that Cu is embedded in g-C3N4 in the form of single atoms.
[0094] Figure 3 FTIR graph of carbon nitride and copper-doped carbon nitride nanocomposite prepared in Example 1 of the present invention.
[0095] from Figure 3 It can be seen that in the spectrum of g-C3N4, 3000~3500, 1110~1700cm- 1 The broad band between 808cm- 1 The peaks at are attributed to the stretching vibration of amino group NH or adsorbed water molecule OH, the vibration of aromatic CN heterocyclic skeleton and the characteristic peaks of triazine ring.
[0096] With the increase of metal content in Cu-g-C3N4, the 1 The additional band at the position gradually strengthened, which was attributed to the stretching vibration of the -C≡N group. In addition, no carbonyl group was detected in Cu-doped g-C3N4. In summary, the addition of Cu inhibited the growth of g-C3N4 during the polycondensation of melamine and induced the generation of defects.
[0097] Figure 4 This is the XPS graph of the metallic copper of the copper-doped carbon nitride nanocomposite material prepared in Example 1 of the present invention. Figure 4 It can be seen that there are two strong peaks at 932.3 and 952.3 eV, and the spin-orbit splitting is 20.0 eV, corresponding to Cu 0 / Cu + Cu2p 3 / 2 and Cu2p 1 / 2 Characteristic peaks indicate that Cu 2+ The absence of satellite peaks near 942 eV also indicates that there is no Cu in the Cu-g-C3N4 nanocomposite. 2+ The Auger electron spectrum of Cu LMM shows a small peak at 566.8eV and a strong peak at 571.2eV, revealing that Cu in the Cu-g-C3N4 nanocomposite 0 and Cu + Further evidence that Cu 0 existence.
[0098] Figure 5 The LSV curve of the electrocatalytic CO2 reduction of the carbon nitride and copper-doped carbon nitride nanocomposite prepared in Example 1 of the present invention. Figure 5 It can be seen that Cu-g-C3N4 has a more positive starting potential than g-C3N4. In addition, the Cu-g-C3N4 nanocomposite catalyst exhibits the largest reduction current density in the entire potential range, which indicates that the Cu-g-C3N4 nanocomposite has the highest CO2 reduction activity.
[0099] Figure 6 The Faraday efficiency diagram of the electrocatalytic CO2 reduction to ethanol produced by the carbon nitride and copper-doped carbon nitride nanocomposite prepared in Example 1 of the present invention at different voltages. Figure 6 It can be seen that in a CO2-saturated 0.5M KHCO3 solution, the applied potential is in the range of -0.8 to -1.1V (vs.RHE), and the g-C3N4 catalyzes the reduction of CO2 mainly to CO, with the highest Faraday efficiency of CO reaching 41%. This is because the g-C3N4 structure contains a large amount of pyridinic nitrogen, which is very effective for CO * The binding energy of Cu and carbon nitride is weak and helps desorption of CO, so the selectivity of CO is very high; while the Cu-g-C3N4 catalyst can effectively inhibit the hydrogen evolution reaction at low applied potential and show high selectivity for C2H5OH. At a potential of -0.9V (vs.RHE), the ethanol Faradaic efficiency reaches 53.44%. This result shows that the tandem catalysis of Cu and carbon nitride can effectively improve the reduction of CO2 to C by copper-based catalysts. 2+ Activity and selectivity of the product ethanol.
[0100] The copper-doped carbon nitride nanocomposite prepared by the present invention utilizes the interlayer stacking of g-C3N4 aromatic fragments to load the metal copper single atom, which can make Cu in a stable oxidation state while increasing the specific surface area, and the presence of the metal copper single atom site promotes CC coupling. The metal copper-doped carbon nitride nanocomposite prepared by the present invention can realize the efficient conversion of CO2 to ethanol, and the Faraday efficiency is greater than 50% in a wide voltage range, and has broad application value.
[0101] The present invention is described above by way of example in conjunction with the accompanying drawings. It is obvious that the implementation of the present invention is not limited to the above-mentioned method. As long as various improvements are made using the method concept and technical solution of the present invention, or the concept and technical solution of the present invention are directly applied to other occasions without improvement, they are all within the protection scope of the present invention.
Claims
1. A method for preparing a copper-doped carbon nitride nanocomposite material, comprising the following steps: Step 1: Preparation of carbon nitride precursor 1.1 Dissolve melamine in deionized water to obtain an aqueous solution of melamine; 1.2 Then, a metallic copper salt is added to the aqueous solution of melamine and stirred to obtain a mixture; 1.3 raising the temperature of the mixture to 100° C. to evaporate water, and after the water is evaporated and removed, drying is performed to obtain a carbon nitride precursor; Step 2: Preparation of copper-doped carbon nitride nanocomposites 2.1 Finely grind the obtained carbon nitride precursor, and heat and calcine under the protection of N2 atmosphere to obtain the product; 2.2 After the product of step 2.1 is cooled to room temperature, the product is washed multiple times with deionized water and anhydrous ethanol to obtain the preparation of copper-doped carbon nitride nanocomposite material.
2. The method for preparing the copper-doped carbon nitride nanocomposite material according to claim 1, characterized in that: In the step 1.1, melamine is dissolved in deionized water at 80° C., and the addition ratio of melamine to deionized water is 1.0-3.0 g: 25-100 mL.
3. The method for preparing the copper-doped carbon nitride nanocomposite material according to claim 1, characterized in that: In the step 1.2, after the copper metal salt is added to the melamine water solution, the mass fraction of the copper metal salt is 1-5%; the stirring time is 30-40 minutes; In the step 1.3, after the water is evaporated away, the mixture is dried in an oven at 60°C.
4. The method for preparing the copper-doped carbon nitride nanocomposite material according to claim 1, characterized in that: In the step 2.1, the temperature is raised and calcined at a heating rate of 5-10°C / min to 500-550°C and calcined for 3-6 hours.
5. The method for preparing the copper-doped carbon nitride nanocomposite material according to claim 1, characterized in that: In the step 2.2, the product is washed multiple times with deionized water and anhydrous ethanol, that is, washed three times with deionized water and washed twice with anhydrous ethanol.
6. A copper-doped carbon nitride nanocomposite material, characterized in that: The invention is prepared according to the preparation method described in any one of claims 1 to 5.
7. Use of the copper-doped carbon nitride nanocomposite material according to claim 6 in electrocatalytic carbon dioxide reduction, characterized in that: Electrode materials were prepared using copper-doped carbon nitride nanocomposites as catalysts for electrocatalytic carbon dioxide reduction.
8. The use of the copper-doped carbon nitride nanocomposite material in electrocatalytic carbon dioxide reduction according to claim 7, characterized in that: The specific operation includes the following steps: The copper-doped carbon nitride nanocomposite material is dispersed in a mixed solution of ethanol and naphthol film ethanol dispersion, and drop-coated on carbon paper as a working electrode, an Ag / AgCl electrode as a reference electrode, and a platinum sheet as a counter electrode; the cathode electrolyte is a CO2-saturated bicarbonate solution.
9. The use of the copper-doped carbon nitride nanocomposite material in electrocatalytic carbon dioxide reduction according to claim 8, characterized in that: The electrolyte of the cathode is one of 0.1-1M KHCO3 solution, NaHCO3 solution, CsHCO3 solution and LiHCO3 solution.
10. The use of the copper-doped carbon nitride nanocomposite material in electrocatalytic carbon dioxide reduction according to claim 8, characterized in that: The loading amount of the copper-doped carbon nitride nanocomposite material is 0.5-2 mg / cm 2 .
Citation Information
Cited By
Preparation of a highly active double heteroatom-doped carbon nitride nanozyme and its colorimetric detection application
CN119735174A
Copper-based nano carbon nitride material, synthesis method and method for electrochemically detecting perfluoro and polyfluoroalkyl compounds by using copper-based nano carbon nitride material
CN120587475A
Copper-based nanocarbon nitride materials, synthesis methods, and methods of electrochemically detecting perfluoro- and polyfluoroalkyl substances
CN120587475B
